Temperature effects on the transition from Lomer-Cottrell locks to deformation twinning in a Ni-Co-based superalloy. (December 2016) - Qi, Dongqing; Fu, Baidong; Du, Kui; Yao, Tingting; Cui, Chuanyong; Zhang, Jianxin; Ye, Hengqiang
Abstract: Deformation mechanisms of a Ni-Co-based superalloy at various temperatures were investigated with aberration corrected and conventional transmission electron microscopes. When deformed at intermediate temperature, Lomer-Cottrell locks were formed in primary γ′ precipitates in this superalloy; at high temperatures, however, microtwins become prominent. The transition from Lomer-Cottrell locks to microtwins with temperature increase is discussed, in particular, on the reordering process in the ordered γ′ precipitates during the deformation twinning. Graphical abstract: